Cyclosporin A inhibits lymphokine production but not the responses of macrophages to lymphokines. - Thomson, A W (1983)
Cyclosporin A (Cs A) exerted a dose-related inhibitory effect on antigen (ovalbumin, OVA) and phytohaemagglutinin (PHA)-induced transformation of guinea-pig lymph node cells (LNC). Whereas 0.05 micrograms/ml was sufficient to depress these responses markedly, it required 100-fold this concentration of Cs A to inhibit the production of lymphocyte activating factor (LAF) by lipopolysaccharide (LPS) stimulated peritoneal macrophages. Addition of Cs A together with insoluble concanavalin A (iCon A) to LNC cultures resulted in suppressed lymphokine production, as assessed by measurement of migration inhibition factor (MIF), the generation of macrophage procoagulant activity (MPCA) and the release of lymphocyte-derived-macrophage chemotactic factor (LDCF). Cs A also inhibited MIF and procoagulant production by sensitized peritoneal exudate cells in response to antigen, at the same concentrations which blocked lymphocyte transformation. In contrast, Cs A had no direct effect on the migration of peritoneal cells from capillary tubes, or on the responses of macrophages to preformed MIF, the lymphokine inducing MPCA or LDCF. Overnight incubation of macrophages with Cs A did, however, result in mild inhibition of their basal level of procoagulant activity.